Internal audit of banks: methodological model for reducing credit risk (Logit model) - Lambekova, A.N.; Temirbekova, L.A.; Syzdykova, E.Zh. (BUKETOV BUSINESS REVIEW, 2020)
Object: The purpose of the research work is to justify the application of a model that allows assessing the probability of a borrower's default and to propose including in the work plan and internal audit program an assessment of the probability of a borrower's default to reduce credit risk. Methods: The article uses quantitative data, statistical model (Logit model). Findings: As a result, during the audit of the banks' debt portfolio, the Logit model was used to assess the probability of a borrower's default. The ROC curve of this Logit model allows you to predict the default situation of the borrower for risk management purposes. Therefore, it is proposed to include an assessment of the probability of default of the borrower based on the model in the work plan and internal audit program. In conclusion, a risk-based internal audit system will help ensure the financial stability. Conclusions: In conclusion, a risk-based internal audit system will help ensure the financial stability. Since we evaluated the debt portfolio and found that the Logit model, which was used to predict the probability of default of borrowers, can prevent risks. This is evidenced by the ROC curve of the Logit model for predicting the probability of default.